Elevated expression of prostaglandin receptor and increased release of prostaglandin E(2) maintain the survival of CD45RO(+) T cells in the inflamed human pleural space - Pace, Elisabetta (Blackwell Science Inc, 2007)
Throughout the body, the distribution and differentiation of T-cell subsets varies in a way that optimizes host responses. The role of activation-induced cell death (AICD) in altering the distribution of T-lymphocyte subsets at an immune or inflammatory sites has been unexplored. The objective of this study was to assess whether pleural macrophages modulate AICD of specific pleural T-lymphocyte subsets. We found that pleural T-lymphocytes spontaneously undergo apoptosis, which is associated to increased expression of both FAS and FAS ligand, to decreased expression of Bcl 2 and to caspase 8 and 3 activation. While pleural T lymphocytes were partly protected from apoptosis, autologous peripheral blood T lymphocytes increased their apoptosis when cultured with exudative pleural fluids. Pleural CD45RO(+) T cells, in comparison to pleural CD45RA(+) T cells, were more susceptible to apoptosis, but were preferentially protected by exudative pleural fluids. Pleural prostaglandin E 2 (PGE(2)) was implicated in protecting T-lymphocytes from apoptosis because exudative pleural T lymphocytes highly express PGE(2) receptors, and because exudative pleural fluid contained high concentrations of PGE(2). Activated pleural macrophages released PGE(2) and reduced the spontaneous apoptosis of pleural T lymphocytes and depletion of PGE(2) from pleural fluids decreased this protective effect. This study demonstrates that PGE(2), released in the pleural fluids following pleural macrophage activation, prolongs the survival of specific T-cell subsets, resulting in differentiation of the T-cell repertoire within the inflamed pleural space.